CpcM Posttranslationally Methylates Asparagine-71/72 of Phycobiliprotein Beta Subunits in Synechococcus sp. Strain PCC 7002 and Synechocystis sp. Strain PCC 6803 - Shen, Gaozhong (American Society for Microbiology (ASM), 2008)
Cyanobacteria produce phycobilisomes, which are macromolecular light-harvesting complexes mostly assembled from phycobiliproteins. Phycobiliprotein beta subunits contain a highly conserved γ-N-methylasparagine residue, which results from the posttranslational modification of Asn71/72. Through comparative genomic analyses, we identified a gene, denoted cpcM, that (i) encodes a protein with sequence similarity to other S-adenosylmethionine-dependent methyltransferases, (ii) is found in all sequenced cyanobacterial genomes, and (iii) often occurs near genes encoding phycobiliproteins in cyanobacterial genomes. The cpcM genes of Synechococcus sp. strain PCC 7002 and Synechocystis sp. strain PCC 6803 were insertionally inactivated. Mass spectrometric analyses of phycobiliproteins isolated from the mutants confirmed that the CpcB, ApcB, and ApcF were 14 Da lighter than their wild-type counterparts. Trypsin digestion and mass analyses of phycobiliproteins isolated from the mutants showed that tryptic peptides from phycocyanin that included Asn72 were also 14 Da lighter than the equivalent peptides from wild-type strains. Thus, CpcM is the methyltransferase that modifies the amide nitrogen of Asn71/72 of CpcB, ApcB, and ApcF. When cells were grown at low light intensity, the cpcM mutants were phenotypically similar to the wild-type strains. However, the mutants were sensitive to high-light stress, and the cpcM mutant of Synechocystis sp. strain PCC 6803 was unable to grow at moderately high light intensities. Fluorescence emission measurements showed that the ability to perform state transitions was impaired in the cpcM mutants and suggested that energy transfer from phycobiliproteins to the photosystems was also less efficient. The possible functions of asparagine N methylation of phycobiliproteins are discussed.